Webinar series 4: international webinar and training for inbound and outbound students, faculty of pharmacy, UiTM. 4 & 10 September, 2025 - Karuppannan, Mahmathi (Faculty of Pharmacy, 2025)
The inbound and outbound student’s webinar have been conducted consecutively for the fourth year as a students exchange program between the partnering universities. These programs were steered by the Continuous Professional Development (CPD) team of the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM). The program started with a keynote addressed by Assoc. Prof. Dr. Fazleen Haslinda Mohd Hatta, Deputy Dean, ICAN, Faculty of Pharmacy. This was followed by, Professor Dr. P. Shanmugasundram, Dean, School of Pharmaceutical Sciences, Vels Institute of Science, Technology & Advanced Studies (VISTAS), Chennai, India who delivered the program orientation to the participants.